2012
DOI: 10.1371/journal.pone.0049809
|View full text |Cite
|
Sign up to set email alerts
|

Giant Robber Crabs Monitored from Space: GPS-Based Telemetric Studies on Christmas Island (Indian Ocean)

Abstract: We investigated the navigational capabilities of the world's largest land-living arthropod, the giant robber crab Birgus latro (Anomura, Coenobitidae); this crab reaches 4 kg in weight and can reach an age of up to 60 years. Populations are distributed over small Indo-Pacific islands of the tropics, including Christmas Island (Indian Ocean). Although this species has served as a crustacean model to explore anatomical, physiological, and ecological aspects of terrestrial adaptations, few behavioral analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
(55 reference statements)
3
18
0
Order By: Relevance
“…Wolff and coworkers (2017) observed that insects with elaborate navigational skills display elaborate mushroom bodies and suggested that place memory is likely to be processed in the crustacean hemiellipsoid body as well as in the insect mushroom body. This hypothesis fits well with the expansion of the hemiellipsoid body in crustaceans such as the coconut crab Birgus latro (Krieger et al, ) for which a seminomadic behavior characterized by territorial phases coupled with phases involving elaborate navigational skills have been reported (Krieger, Grandy, et al, ). A similar correlation between comparably large hemiellipsoid bodies (original pictures from M. Schmidt; modified from Schmidt & Ache, ; combined and equally scaled in Harzsch & Krieger, ) and lifestyles involving elaborate spatial memory (review in Sandeman et al, ) can be assigned also to the seminomadic spiny lobster Panulirus argus .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Wolff and coworkers (2017) observed that insects with elaborate navigational skills display elaborate mushroom bodies and suggested that place memory is likely to be processed in the crustacean hemiellipsoid body as well as in the insect mushroom body. This hypothesis fits well with the expansion of the hemiellipsoid body in crustaceans such as the coconut crab Birgus latro (Krieger et al, ) for which a seminomadic behavior characterized by territorial phases coupled with phases involving elaborate navigational skills have been reported (Krieger, Grandy, et al, ). A similar correlation between comparably large hemiellipsoid bodies (original pictures from M. Schmidt; modified from Schmidt & Ache, ; combined and equally scaled in Harzsch & Krieger, ) and lifestyles involving elaborate spatial memory (review in Sandeman et al, ) can be assigned also to the seminomadic spiny lobster Panulirus argus .…”
Section: Discussionsupporting
confidence: 84%
“…These skills suggest sophisticated learning capabilities with regard to communication which might be reflected in a very pronounced hemiellipsoid body. However, since it is very territorial (Chockley & Mary, ), S. hispidus is not considered to display sophisticated navigational skills which are often but not exclusively linked to the need of spatial learning and thus effective multimodal association centers like the mushroom bodies in honey bees or ants (Hexapoda) (Grob, Fleischmann, Grübel, Wehner, & Rössler, ; Menzel & Müller, ; Webb & Wystrach, ), or the hemiellipsoid bodies in mantis shrimps (Stomatopoda) (Wolff et al, ), spiny lobsters (Achelata) (Boles & Lohmann, ; Steullet et al, ), or robber crabs (Anomala) (Krieger et al, , ). A highly territorial lifestyle, as reported for the banded cleaner shrimp, is a behavior essentially dependent on the realization of good place memory, so that spatial learning could play a major role for these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Sections of the higher integrative centers (i.e. hemiellipsoid body and terminal medulla) ( A–G ) and horizontal sections of the olfactory neuropil ( a–g ) labeled with different sets of antibodies (see below), in several malacostracan species: Nebalia herbstii ( Aa ), Leptostraca, from Kenning and Harzsch (2013); Kenning et al (2013), Penaeus vannamei ( Bb ), Dendrobranchiata, from Meth et al (2017), Saduria entomon ( Cc ), Isopoda, from Kenning and Harzsch (2013), Palaemon elegans ( Dd ) and Rimicaris exoculata ( Ee ) (Caridea, this study), Carcinus maenas ( Ff ), Brachyura, from Krieger et al (2012b) and Birgus latro ( Gg ), Anomala, from Krieger et al (2010). Markers: a , SYNir; B , SYNir +RFair; b , SYNir +RFair + NUC; Cc ), SYNir +5 HTir; A,d,e, SYNir +ASTir; D,E,F-g, SYNir +ASTir + NUC.…”
Section: Resultsmentioning
confidence: 99%
“…We are interested in exploring adaptive changes of crustacean brain structures that have occurred during their evolutionary radiation into particular habitats and their adoption of specific life styles (e.g. Harzsch et al, 2011; Kenning and Harzsch, 2013; Krieger et al, 2015; Krieger et al, 2012b; Krieger et al, 2010; Meth et al, 2017). Differential investment in certain brain neuropils might reflect the sensory landscape which a certain crustacean species typically exploits, so that studying an animal’s brain anatomy may allow for predictions related to its ecology and lifestyle (Sandeman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Passive integrated transponder (PIT) tags have also been applied to the coconut crab Sato et al, 2013). In addition, Krieger et al, (2012) used GPSbased telemetric studies to examine their migration behavior. However, natural features or markings have been used to identify individuals of some crustacean species (MacDiarmid et al, 2005;Gallardo-Escarate et al, 2007;Gosselin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%